Patient's Satisfaction in Utilizing Public Health Center Services during the COVID-19 Pandemic Based on Gender, Age, Education Level, and Occupation - Ristya Widi Endah Yani; Abu Khoiri; Taufan Bramantoro (ACHSM, 2023)
A public health center is at the forefront of breaking the COVID-19 chain. Limiting the number of patients accessing care during the pandemic is thought to affect patient satisfaction with the quality of service at the public health center during the COVID-19 pandemic. This study aims to know the level of satisfaction of patients visiting a health center based on gender, age, education level, and profession criteria during the COVID-19 pandemic in Sumbersari District, Indonesia. This study used an analytical observational study method for visitors of the Sumbersari Public Health Center in February-March 2021. The population was 126,279 people visiting Sumbersari Public Health Center, meaning a purposive sampling requires 100 people to participate. The research variables were gender, age, education level, occupation, and the patient's satisfaction. The measuring instrument used was a questionnaire. The data were analyzed descriptively using logistic regression test. There is no effect of gender and age on patient satisfaction (p> 0.05). There is an effect of the level of education on patient satisfaction (p <0.05) with OR = 3.32. There is an effect of work on patient satisfaction (p <0.05) with OR = 0.054, meaning that respondents who work, the chance to feel dissatisfied is 18.5 times greater than respondents who do not work.